2014
DOI: 10.1155/2014/459747
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Stent Placement Increases the Risk for Developing BK Viremia after Kidney Transplantation

Abstract: The placement of ureteral stent (UrSt) at kidney transplantation reduces major urological complications but increases the risk for developing nephropathy from the BK virus. It is unclear whether UrSt placement increases nephropathy risk by increasing risk of precursor viral replication or by other mechanisms. We retrospectively investigated whether UrSt placement increased the risk for developing BK Viremia (BKVM) in adult and pediatric kidney transplants performed at the University of Florida between July 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…In addition, multivariate analysis revealed that immediate graft function is associated with increased rate of BK viremia. These findings support results from previous studies performed on smaller populations and affirm the need for greater vigilance for BK‐related kidney disease post‐transplant in patients receiving ureteral stent placement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, multivariate analysis revealed that immediate graft function is associated with increased rate of BK viremia. These findings support results from previous studies performed on smaller populations and affirm the need for greater vigilance for BK‐related kidney disease post‐transplant in patients receiving ureteral stent placement.…”
Section: Discussionsupporting
confidence: 90%
“…The study by Hashim et al . in 2014, which included one of the present study authors but at a separate center, used a retrospective study design with a larger study population of 621 patients and reported an increased adjusted risk of both BK viruria (adjusted OR, 1.67; P = 0.04) and BK viremia (adjusted OR, 1.55; P = 0.04).…”
Section: Discussionmentioning
confidence: 98%
“…In a single centre retrospective study, comparing 295 RTR who had ureteric stents placed was compared with 326 without stent as per the surgeon's preference. BK viremia was seen in 22% in those with stent versus 16% without stent ( P = 0.05) . However, ureteric stent is the current standard practice as it reduces immediate post‐transplant urologic complications.…”
Section: Bk Virus Nephropathymentioning
confidence: 99%
“…53 Additionally, literature suggests that ureteral stenting during kidney transplant increases the risk of polyomavirus BK viremia and viruria. 54 OTHER UROLOGIC CONSIDERATIONS IN THE KIDNEY TRANSPLANT RECIPIENT UTI in transplant recipients is established with urine culture and treated with antibiotic therapy. Pyelonephritis can present with fever and systemic symptoms, such as abdominal pain, pain over the graft site, nausea, and emesis, and presents harm to the graft through renal parenchymal scarring.…”
Section: Immunosuppressionmentioning
confidence: 99%